Application of Wordwall Learning Media in Improving Students’ Interest in Islamic Religion Education at State Senior High School 1 Talaga Raya - Hastiana, Hastiana; Maudin, Maudin; Darmayanti, Darmayanti (Journal of English Language and Education, 2025)
A significant contributing factor to the lack of interest in learning Islamic Religious Education at SMA Negeri 1 Talaga Raya is the absence of interactive learning materials used in the classroom. The purpose of this study was to determine how well Wordwall learning materials could increase the interest of Class XI students at SMA Negeri 1 Talaga Raya in learning Islamic Religious Education. The methodology employed in this study was Classroom Action Research (CAR), which was conducted in two cycles. Each cycle included planning, implementation, observation, and reflection. The study's findings revealed that, after using Wordwall learning materials, students' enthusiasm for learning increased. This is evident from the comparative results of the learning interest percentage indicators in Class XI at SMA Negeri 1 Talaga Raya. The indicators reached the success threshold, with results exceeding the researcher’s benchmark of 70%.